IMPROVED UNDERSTANDING OF INDONESIA'S BORDER SITUATION IN NUSA TENGGARA TIMUR PROVINCE WITH TIMOR LESTE IN OECUSSI DISTRICT - Posma Sariguna Johnson Kennedy; Suzanna Josephine L. Tobing; Rutman Lumban Toruan; Anton Nomleni; Santi Lina Siregar (JURNAL PENGABDIAN MANDIRI, 2022)
This study and community service activity aims to increase understanding of a topic or problem regarding the situation of the Indonesian Republic Border in the Province of Nusa Tenggara Timur (NTT) and the Democratic Republic of Timor Leste (RDTL) in the Oecussi District. The activity was carried out using a discussion method by meeting related sources in the border area, namely Timor Tengah Utara (TTU), Wini State Border Post (TTU), Napan State Border Post (TTU), and Oecusse Border Post (RDTL). The writing method uses a quantitative descriptive approach using various literature reviews and several data sources as secondary data, apart from the results of various discussions conducted at the activity location. There are ethnic similarities between Indonesia and Timor Leste because they have a common ancestor. Even though they are one tribe/descendant, conflicts often occur between them due to the struggle for land at the border. The governments of the two countries need to carry out dialogue and negotiations to resolve border social conflicts that occur in villages whose land status is still in dispute in the border areas.